2020
DOI: 10.3390/insects11020086
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Vitis Cultivars, Rootstocks, and Species Expressing Resistance to a Planococcus Mealybug

Abstract: Mealybugs cause economic loss to vineyards through physical damage, fouling fruit and leaves with honeydew, and the transmission of viruses. Planococcus ficus is one of several mealybug species in vineyards, and one that causes economic damage over a relatively large global range. To develop novel management tools, host resistance to P. ficus, which has not previously been identified for any grape cultivars, was studied. Ten grape lines (species, cultivars, and rootstocks) were evaluated for P. ficus resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Principal component analysis using chemicals extracted from leaves collected from several cultivars in the field suggests that a difference exists between resistant and susceptible cultivars [ 19 ], but whether this represents a response to scale insects or is simply correlated with an apparent resistance difference requires further study. Riesling cultivars showed very little change in gene expression following relatively short exposures (6 and 96 h) to the mealybug Planococcus ficus (Signoret) [ 38 ], while other cultivars may have some tolerance or resistance to mealybugs [ 39 ]. Lawo, Weingart, Schuhmacher and Forneck [ 9 ] indicate that volatiles varied when phylloxera were present on a single resistant cultivar, but the time over which this change occurred was relatively short.…”
Section: Discussionmentioning
confidence: 99%
“…Principal component analysis using chemicals extracted from leaves collected from several cultivars in the field suggests that a difference exists between resistant and susceptible cultivars [ 19 ], but whether this represents a response to scale insects or is simply correlated with an apparent resistance difference requires further study. Riesling cultivars showed very little change in gene expression following relatively short exposures (6 and 96 h) to the mealybug Planococcus ficus (Signoret) [ 38 ], while other cultivars may have some tolerance or resistance to mealybugs [ 39 ]. Lawo, Weingart, Schuhmacher and Forneck [ 9 ] indicate that volatiles varied when phylloxera were present on a single resistant cultivar, but the time over which this change occurred was relatively short.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, Pa. corni was shown to transmit GLRaV-1 but not GLRaV-3 [ 21 , 32 , 39 ], though GLRaV-3 transmission by this species was reported in Washington State, USA [ 40 ]. Variations of transmission rates within a given vector species are likely due to a combined effect of experimental conditions, vector and virus intraspecific variability, and differential susceptibility of grapevine varieties to either the virus or vector [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Damien et al 2017;Michaud 2018;Santoiemma et al 2020). The tolerance of rootstocks and cultivars to P. ficus infestations has been recently investigated in potted plants (Naegele et al 2020), indicating the cultivars Chardonnay and Cabernet Sauvignon as favorable substrates for VMB population growth, whereas the rootstocks IAC 572, 10-17A and RS-3 reduced the pest development. Naegele et al (2020) also suggested that physical and/ or chemical features may affect mealybug settling, feeding and host attractiveness, being therefore involved in the resistance mechanisms (antibiosis and antixenosis).…”
Section: Cultural Controlmentioning
confidence: 99%
“…The tolerance of rootstocks and cultivars to P. ficus infestations has been recently investigated in potted plants (Naegele et al 2020), indicating the cultivars Chardonnay and Cabernet Sauvignon as favorable substrates for VMB population growth, whereas the rootstocks IAC 572, 10-17A and RS-3 reduced the pest development. Naegele et al (2020) also suggested that physical and/ or chemical features may affect mealybug settling, feeding and host attractiveness, being therefore involved in the resistance mechanisms (antibiosis and antixenosis). However, grapevine plants displayed a weak transcriptional response to P. ficus feeding, with a single gene, pathogenesis-related protein 1, being expressed as a response of mealybug attack (Timm and Reineke 2014).…”
Section: Cultural Controlmentioning
confidence: 99%
See 1 more Smart Citation